Mapping the Health and Medical Research Excellence in Nepal: A Study of High-Cited Papers During 1994-2023 - Vaishya, Raju; Gupta, Brij Mohan; Mamdapur, Ghouse Modin Nabeesab; K.S., Ali; Vaish, Abhishek; Joshi, Pramod; Hamal, Pawan Kumar (Journal of Nepal Health Research Council, 2024)
Background: A bibliometric analysis was performed to map the current status and development trends in medical research in Nepal. It aims to visualize research hotspots within this field and provide effective guidance for future research directions. Methods: A systematic search of the Scopus database was performed to identify high-cited papers (HCPs) on medical research in Nepal between January 1, 1994, and December 31, 2023. Bibliometrics techniques were applied to analyze the publication dates, countries, institutions, journals, authors, and research hotspots. Statistical analysis and visualization were carried output by MS-Excel and VOSviewer software. Results: A total of 326 HCPs were identified that have received 100 to 10719 citations and registered 223.05 Citations Per Paper (CPP). The 47.54% and 95.40% share of the 326 HCPs have received external funding support and are involved in international collaboration, respectively. The 15892 (417 from Nepal) authors, affiliated to 12830 (177 from Nepal) organizations and published in 138 journals participated in 326 HCPs from Nepal. USA (60.45% share) and India. (51.45% share) were the most collaborative countries, while Spain (1609.15 CPP) and Mexico (1597.08 CPP) made the largest citation impact in collaboration with Nepal. C.L. Ranabhat (n=27) and B. Sathian (n=26) were the most productive authors, while D. Acharya (3652.29 and 16.5), and S. Bhattarai (2880.11 and 13.01) registered the highest citation impact (CPP and RCI). Tribhuvan University, Kathmandu (n=72) and Nepal Health Research Council, Kathmandu (n=34) were the most productive organizations, while Kathmandu University (3652.29 and 16.5) and Nepal Academy of Science and Technology, Lalitpur (2941.67 and 13.29) registered the highest citation impact (CPP and RCI). The Lancet (n=75) and British Medical Journal (n=11) were the most productive journals, while The Lancet Neurology (1749.5 CPP), and The Lancet (1371.13 CPP) registered the highest average citations impact. B. Basnyat has the most citation as first author in health and medical research. Conclusions: The present study offers an overview of research characteristics and trends of medical research output in Nepal. It identifies main contributors, core journals, and significant subject topics. The study hopes to assist researchers and practitioners in comprehending the development and trends of medical research in Nepal and discovering potential directions for future research. Keywords: Bibliometric methods; citations; collaboration; high-cited papers; medical research.